The 1935 portuguese reinforced concrete code: Background, sources and authors - J. P. Delgado (2019)
The object of the paper is the 1935 Portuguese Reinforced Concrete Code (RBA), approved two years after the establishment of the Estado Novo regime. The research takes this background as relevant, as the code was a foundation for a programme of public works. The starting point is the report that prefaces the regulations. It clarifies the methodology adopted for defining design standards, which was to compare 14 of the most advanced regulations. The technical report also identifies all of the authors of the RBA, who were six leading structural engineers. The paper aims at a threefold relevance. Firstly, to understand the method used for drafting the code, and, consequently, to comprehend the dissemination of reinforced concrete. Secondly, to throw light on how the issues of development were addressed in the 1930s. And thirdly, to understand how European countries dealt with building modernization during that years. (c) 2019 Taylor & Francis Group, London.